Cumulative occupational mechanical exposures during working life and risk of sickness absence and disability pension: prospective cohort study - Emil Sundstrup; Åse Marie Hansen; Erik Lykke Mortensen; Otto Melchior Poulsen; Thomas Clausen; Reiner Rugulies; Anne Møller; Lars L Andersen (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The aim of this study was to determine the prospective association of cumulative mechanical exposure during working life with health-related labor market outcomes. METHODS: This prospective cohort study combines data from 5076 older workers (age 49-63 years) from the Copenhagen Aging and Midlife Biobank with a job exposure matrix and a national register containing information on social transfer payment. By coding individual job histories from the Danish version of ISCO-codes (International Standard Classification of Occupations), we calculated cumulative occupational mechanical exposures from a JEM for ton-years (lifting 1000 kg each day in one year), lifting-years (lifting loads weighing ≥20 kg >10 times each day in one year), kneeling-years (kneeling for one hour each day in one year) and vibration-years (whole-body vibration for one hour each day in one year). Cox-regression analyses estimated the relative risk of register-based long-term sickness absence (LTSA) and disability pension with cumulative occupational mechanical exposures throughout working life. Analyses were censored for competing events and adjusted for multiple confounders. RESULTS: During the follow-up period, 970 persons (19.3%) had ≥1 episode of LTSA and 85 persons (1.7%) were granted a disability pension. Number of ton-, lifting- and kneeling-years showed an exposure-response association with increased risk of LTSA (P<0.0001). In addition, both long term [≥20 years; hazard ratio (HR) 1.76 95% CI 1.39-2.22] and short term (<10 years; HR 1.20 95% CI 1.02-1.41) exposure to kneeling work increased the risk of LTSA. Lifting-years, but not the other mechanical exposures, were associated with risk of disability pension (HR 1.75 95% CI 1.01-3.04). CONCLUSIONS: Cumulative occupational mechanical exposures during working life - such as lifting and kneeling work - increased the risk of LTSA. Importantly, being exposed to lifting increased the risk of disability pension.